G395 More and More Parents are taking their Medicines for Children. (7th April 2014) - Tuthill, DP; Sammons, H; Tomlin, S; Partridge, L; Olson, K; Fox, A
Abstract : Background: Medicines for Children (MfC) is a joint venture between the RCPCH, NPPG (Neonatal Paediatric Pharmacists Group) and the charity Wellchild. It aims to provide accessible, unbiased high quality information for parents and carers who need to administer medication to their children. It has two main arms; it's website and printable written information sheets. 172 leaflets and videos already exist online at www.medicinesforchildren.org.uk . A 4 stage production process for the leaflets is followed to ensure a high quality and standardisation according to the format. The leaflets are Information Certified by the Plain English Campaign and MfC has been awarded the NHS Information Standard certified member status. Some institutions are utilising them as a resource to meet the medicines information requirements of the Care Quality Commission. Aims: To evaluate uptake by website usage. To assess parental views. Methods: Analysis of website traffic using Google Analytics. Consultation group of parents qualitatively exploring to what extent MfC met their needs. Results: Website analysis in 4 month periods: Consultation group (n = 14) found the resource "accessible", "useful", "easy to understand", "attractive" and "trustworthy". All would recommend it to others. They appreciated that the production process was transparent. Conclusions: MfC is a major new reliable information resource that has had a sixfold increase in use over the last 2 years. It is valued and believed by parents, who felt that the Information Standard gave it appropriate trustworthiness. This combined approach provides a readily available, high quality, uptodate free to use resource for families, pharmacists and paediatricians. It's good to see that more and more parents are taking their "Medicines for Children"!